Kontinuitas Pembelajaran Jarak Jauh Atau Online Bagi Peserta Didik Pendidikan Kesetaraan Paket B Dan C Pada PKBM HARAPAN BANGSA Di Kota Kupang - Sogen, Yosephine Katharina; Co'o, Serilius; Simbolon, Gallex (Education For All, 2022)
Abstract Learning problems during the Covid-19 pandemic for various levels of education experienced many problems. This study wants to examine various learning problems in online PKBM and the use of certain applications to support the teaching and learning process in community education. The purpose of this study is to explain or analyze the use of certain applications that provide easy learning and teaching for tutors and students, during the Pandemic. The Se-Tara Daring application through the Learning Management System helps students access learning materials, carry out learning evaluations, and control learning so that the continuity of learning goes well. The results showed that learning activities using the Se-Tara Daring application, which was maximized with Whatsapp Group, Email Id, and mobile phone numbers could support the continuity of learning. The teaching and learning process runs continuously or smoothly and continuously using the Se-Tara Daring application so that it can run well. This research uses the descriptive qualitative research method because this research wants to define, explain and tell a phenomenon or event as it is. This method uses data collection techniques of observation, interviews, and documentation studies. Analysis of the data used is data analysis of Miles and Huberman. The analysis uses data reduction, data presentation, and conclusion drawing. Kata Kunci application, Se-Tara Daring, community study and activity center, learning.